2011
DOI: 10.1182/blood-2011-04-348755
|View full text |Cite
|
Sign up to set email alerts
|

Chronic myeloproliferative neoplasms and subsequent cancer risk: a Danish population-based cohort study

Abstract: Patients with chronic myeloproliferative neoplasms, including essential thrombocythemia (ET), polycythemia vera (PV), and chronic myeloid leukemia (CML), are at increased risk of new hematologic malignancies, but their risk of nonhematologic malignancies remains unknown. In the present study, we assessed the risk of both types of malignancies after an ET, PV, or CML diagnosis. We linked 2 population-based nationwide registries, the Dan-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
159
3
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 152 publications
(175 citation statements)
references
References 26 publications
11
159
3
2
Order By: Relevance
“…Accordingly, myelofibrosis may be featured by clinical, biochemical, and molecular evidence of an aberrant and dysfunctional immune system, 4,48-51 implying a potential risk of autoimmune/autoinflammatory diseases and, in addition, an increased risk of second cancer. 4,52,53 Several observations are supportive for this hypothesis. First, several studies have shown that inflammatory diseases may precede or develop during the course of ET, PV, and myelofibrosis.…”
Section: Does Chronic Inflammation Trigger Clonal Evolution Autoimmusupporting
confidence: 60%
“…Accordingly, myelofibrosis may be featured by clinical, biochemical, and molecular evidence of an aberrant and dysfunctional immune system, 4,48-51 implying a potential risk of autoimmune/autoinflammatory diseases and, in addition, an increased risk of second cancer. 4,52,53 Several observations are supportive for this hypothesis. First, several studies have shown that inflammatory diseases may precede or develop during the course of ET, PV, and myelofibrosis.…”
Section: Does Chronic Inflammation Trigger Clonal Evolution Autoimmusupporting
confidence: 60%
“…In the background, more frequent occurrence of nonhematological malignancies was revealed to be responsible for this adverse survival in our classic MPN cohort. BCR-ABL1 chromosome-negative and positive MPN patients were previously described to present with an increased risk of developing a subsequent nonhematologic cancer (33). According to the general assumption, these subsequent nonhematologic tumors were simply attributed to the application of myelosuppressive regimens.…”
Section: Discussionmentioning
confidence: 99%
“…In Passamonti study, age > 65 years was determined to be a risk factor for developing SPM including leukemia [32] . A Danish study demonstrated that the probability of non hematologic and hematologic malignancies was higher in younger patients (2049 years vs 5069 and > 70 years) [13] . Such conflicting results may be accounted by the differences in the characteristics of patients and other risk factors for SPM in different studies.…”
Section: Discussionmentioning
confidence: 99%
“…The log rank test was statistically significant with a P-value of < 0.01. [13] . Another retrospective study from Italy (n = 331) showed cumulative incidence of SPM of 13% from the time of diagnosis of ET [17] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation